2017
DOI: 10.1259/bjr.20160156
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of dementia with Lewy bodies: can 123I-IMP and 123I-MIBG scintigraphy yield new core features?

Abstract: Objective: Since the clinical symptoms of different types of dementia frequently overlap, especially in the earlier stages at onset, it is difficult to distinguish dementia with Lewy bodies (DLB) from other neurodegenerative dementias based on their clinical manifestations alone. Nuclear medicine imaging has been reported as a high-value index for the objective evaluation and diagnosis of DLB. The aim of this study was to evaluate whether nuclear medicine imaging findings may yield core featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The current literature on perfusion SPECT is limited by lack of pathology-confirmed investigations, small sample sizes, and a handful of studies in MSA, PSP, and CBS. Moreover, given the overlap in perfusion profiles, other techniques (e.g., 123 I-metaiodobenzylguanidine myocardial scintigraphy or DAT imaging) may perform superior to perfusion SPECT in some cases ( 258 ). Multimodal imaging can provide valuable diagnostic information in uncertain cases ( 10 ).…”
Section: Spect Imaging Of Cerebral Perfusion In Parkinsonian Disordermentioning
confidence: 99%
“…The current literature on perfusion SPECT is limited by lack of pathology-confirmed investigations, small sample sizes, and a handful of studies in MSA, PSP, and CBS. Moreover, given the overlap in perfusion profiles, other techniques (e.g., 123 I-metaiodobenzylguanidine myocardial scintigraphy or DAT imaging) may perform superior to perfusion SPECT in some cases ( 258 ). Multimodal imaging can provide valuable diagnostic information in uncertain cases ( 10 ).…”
Section: Spect Imaging Of Cerebral Perfusion In Parkinsonian Disordermentioning
confidence: 99%
“…SPECT imaging using 123 I–metaiodobenzylguanidine, a marker of postganglionic sympathetic innervation, showed reduced cardiac uptake in both DLB and PDD as compared with AD [ 110 , 111 ]. The sensitivity, specificity, and accuracy for the diagnosis of probable DLB is 82.4%, 96.3%, and 92.5%, respectively [ 112 ]; yet, although specific data on PDD are not available, 123 I–metaiodobenzylguanidine imaging is unlikely to differentiate PDD from DLB.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence clearly showed that the approach of moving mainly from the clinical features as markers of disease presented with several limitations [5]. Indeed, clinical core symptoms were reported to appear relatively late in the course of the disease and to overlap with clinical symptoms of other dementing diseases, especially in the earlier stage, thus making difficult to distinguish DLB from other neurodegenerative dementias based on clinical manifestations alone [6]. On the other hand, results of epidemiologic and clinical studies showed that DLB is the second commonest cause of neurodegenerative dementia, and that it progresses more rapidly than other dementing disorders, harboring a poor prognosis due to severe cognitive impairment and parkinsonism [7].…”
Section: Introductionmentioning
confidence: 99%